Cytology as a guide to the presence of chlamydial inclusions in Giemsa-stained conjunctival smears in severe endemic trachoma. - Yoneda, C. (1975)
Microscopical examination of 927 Giemsa-stained conjunctival smears from children with chronic trachoma in southern Tunisia showed 93 (10 per cent.) with typical trachoma (chlamydial) inclusions in epithelial cells. The accompanying cytological features were a useful indicator for inclusions. Inclusions were found only in slides with numerous polymorphonuclear neutrophils (PMNs) and separation of the epithelial cells. When these two features alone were present, 3 per cent. of the smears were inclusion-positive; when many lymphocytes were present also, 25 per cent. were inclusion positive; when other cytological features (plasma cells, macrophages, blastoid, and stem cells) were present as well, 70 per cent. of the smears were inclusion-positive. The occurrence of these sets of cytological features can be a useful guide for selecting smears for intensive examination for chlamydial inclusions. Immunofluorescent (FA) staining and Giemsa staining of 527 pairs of matched smears detected trachoma agent in 67 (13 per cent.); in thirty by both methods, in thirteen by Giemsa staining alone, and in 24 by FA alone. The examination of Giemsa-stained smears for chlamydial inclusions is a useful technique for the diagnosis of trachoma or inclusion conjunctivitis by laboratories that do not have the specialized facilities for the identification of these chlamydial infections by the technically more complex procedures of immunofluorescent staining or isolation in embryonated eggs or tissue cultures.